F8 intron 22 inversions and SNP rs73563631 in unrelated families with severe haemophilia A: clinical features and gene testing implications - Abelleyro, Miguel Martin (2015)
F8 intron 22 inversions (INV22), the commonest cause of severe haemophilia A (HA), are mostly represented by type I (INV22-1) and type II (INV22-2) patterns (4:1) using BclI-fragments´ based techniques such as inverse shifting-PCR (IS-PCR/2008). Using IS-PCR/2008, we identified unusual patterns of the INV22-1 and INV22-2 (characterised by no signals in the diagnostic test and conventional INV22-1/-2 patterns in the complementary test) in patients and carriers from two (0.6%) out of 308 Argentinean families with severe-HA. A theoretical analysis of the 85 SNPs embedded in the relevant BclI-fragments followed by PCR-BclI-RFLP analysis allowed identification of the SNP rs73563631*G allele associated with a new BclI-restriction site in all four patients of Family 1 and 2. Linkage analysis using seven F8-linked-STRs in the two families confirmed two unrelated haplotypes in phase with INV22-1/-2. Screening of 404 X-chromosomes from the Argentinean general population failed to detected SNP rs73563631*G allele (q<0.24%). A new version of the IS-PCR/2008 adding the genotyping of the new patterns (x) of INV22-1/-2 was developed. Clinical/biochemical characteristics (severity and inhibitor risks) of patients with INV22-1x/-2x were virtually equal to canonical INV22s. Our estimations predict the involvement of INV22-1x/-2x in about 2.7% (4/149) of INV22-affected cases worldwide.